Comparison of lenvatinib plus pembrolizumab versus first-line systemic chemotherapy for advanced intrahepatic cholangiocarcinoma: a real-world retrospective study - Yang, Zhenyun; Wu, Weijie; Hu, Zhiwen; Fu, Yizhen; Hu, Zili; Pan, Yangxun; Wang, Juncheng; Chen, Jinbin; Zhou, Zhongguo; Zhang, Yaojun; Chen, Minshan; Hu, Dandan (Frontiers in Immunology, 2024)
BackgroundSystemic chemotherapy (SC) stands the only first-line treatment for advanced intrahepatic cholangiocarcinoma (iCCA) for the past few decades. Immune checkpoint inhibitors (ICIs) have been proved to provide additional benefit in disease control. However, oncological outcome of iCCA remains poor and awaits further improvement with new treatment modalities. Promising results have been observed in lenvatinib plus pembrolizumab (Len-P) as a second-line therapy in iCCA. This study aimed to explore the safety and efficacy of Len-P as a first-line therapy for iCCA patients in real-world clinical practice.MethodsWe retrospectively enrolled 133 patients with advanced iCCA who received Len-P or SC between May 2019 and May 2023. Overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and adverse events (AEs) were compared between the two groups.ResultsThere were 72 patients and 61 patients in the Len-P and SC groups, respectively. The median OS for the Len-P and SC groups was 16.3 and 17.8 months, respectively. The median PFS for the Len-P and SC groups was 8.9 and 11.4 months, respectively. There was no significant difference in ORR and DCR between the Len-P and SC groups (ORR: 22.2% vs. 23%; P=0.92; DCR: 69.4% vs. 77%; P=0.58). Additionally, the overall incidence of AEs was lower in the Len-P group than SC group. Low inflammation-based scores were indicative of favorable outcomes in patients undergoing Len-P therapy.ConclusionThis study demonstrated that Len-P is promising for the treatment of advanced ICC, with highly improved safety. It emerges as a viable treatment alternative for advanced iCCA. Inflammation-based scores show potential utility in identifying individuals likely to benefit from Len-P therapy.